The impact of the working environment on employees performance in hotel / Siti Norsyazwani Mat Wi and Laila Najihah Yahaya - Mat Wi, Siti Norsyazwani; Yahaya, Laila Najihah (2017)
The purpose of this study is to identify the different aspect of working environment in organization and to determine the relationship between the work environment and employees’ performance. The data were collected from previous data that focus on employees in hotel industry. There are three element of working environment which is physical working environment, supervisor support and working hours. The three elements have positive and negative impact on employees’ performance.